Electroanalytical Methods as a Tool for Determining the Antioxidant Capacity in Blood Samples - Fernanda Gonçalves de Oliveira; Thiago da Silveira Alvares; Rodrigo de Siqueira Melo (The Journal of Engineering and Exact Sciences)
Aerobic metabolism is an essential process for energy production in cells, but it also generates reactive oxygen species (ROS), which, in excess, can cause cellular damage and contribute to the development of various diseases, such as cardiovascular diseases, cancer, and neurodegenerative disorders. The balance between ROS and antioxidants is crucial for health, as an imbalance can lead to oxidative stress, a significant risk factor for several clinical conditions. Electroanalytical techniques, such as cyclic voltammetry (CV), square wave voltammetry (SWV), and differential pulse voltammetry (DPV), have proven to be powerful tools for evaluating antioxidant capacity more efficiently and accurately than traditional spectrophotometric methods. These techniques offer notable advantages, such as high sensitivity, simplicity, and the ability to analyze complex biological samples rapidly. CV allows for the analysis of compounds with good sensitivity, DPV stands out for its high precision, while SWV offers excellent resolution and speed, making it ideal for clinical applications. The use of these methodologies has been expanded to analyze antioxidants in various biological matrices, enabling a more accurate assessment of oxidative stress and antioxidant status in specific clinical contexts. Additionally, electrochemical biosensors have become revolutionary tools in clinical diagnostics, allowing real-time monitoring of diseases related to oxidative stress. Innovations such as portable devices and integration with artificial intelligence promise to further enhance accessibility and treatment personalization, despite the challenges involved in device cost and standardization.